2009
DOI: 10.1002/mabi.200800192
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylsilylation of Cellulose in Ionic Liquids

Abstract: Trimethylsilylation of cellulose in different 1,3-dialkylimidazolium ionic liquids (IL) with hexamethyldisilazane (HMDS) as a silylating agent was investigated. Trimethylsilyl (TMSi) cellulose with a degree of substitution (DS) greater than 1 is insoluble in the IL. The maximum DS obtained depends on the nature of the anion. Carboxylate and diethylphosphate counterions gave better results than chloride or thiocyanate, which corresponds to the solubility of HMDS in the IL. Controlled silylation with stoichiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
0
33
0
1
Order By: Relevance
“…It has been reported [196] that carboxylate and diethylphosphate counter-ions give better results than chloride. Furthermore, the solubility of HMDS in the IL increases with the increasing extent of CH x groups in the anion.…”
Section: Etherificationmentioning
confidence: 99%
“…It has been reported [196] that carboxylate and diethylphosphate counter-ions give better results than chloride. Furthermore, the solubility of HMDS in the IL increases with the increasing extent of CH x groups in the anion.…”
Section: Etherificationmentioning
confidence: 99%
“…A vast range of material properties can be accessed with cellulose derivatives by varying the chemical substituents attached to the polysaccharide backbone and their degree of substitution (DS). To cite just one example, solubility can range from hydrocarbon-soluble (trimethylsilylcellulose) (Mormann and Wezstein 2009), to water-soluble (e.g., cellulose monoacetate) (Buchanan et al 1991a, b;Heinze et al 2006), depending primarily on the type and number of substituents. Cellulose derivatives in general also have unique properties that may be highly beneficial for certain applications, for example high biocompatibility for biomedical applications (Edgar 2007;Liebert et al 2009), good clarity for optical films (Edgar et al 2001;Sata et al 2004), and chirality for the separation of enantiomers (Okamoto 2009;Katoh et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…MIM directly facilitates certain reactions and may be successfully used as a cosolvent or additive in derivatization [21,27]. In fact, it has been shown that MIM, which is a precursor for many imidazolium-based ILs, is quite necessary for some reactions to take place at all [28].…”
Section: Introductionmentioning
confidence: 99%